CCAFS at COP18 in Doha, Qatar - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
CCAFS held a side event and participated in the 18th Conference of Parties of the UN Framework Convention on Climate Change (UNFCCC COP18) in Doha, Qatar. 26 November to 7 December 2012. Photo:C.Schubert (CCAFS)